Implementation of Understanding the Qur'an Verses about People with Special Needs by Students at Yari Junior High School Padang - Hidayatul Azizah Gazali; Sefri Auliya (Jurnal Ulunnuha, 2022)
This study aims to reveal the understanding of students at Yari Junior High School Padang on the verses of the Qur'an about people with special needs and their implementation in daily life. This research type is qualitative research in the form of case studies, with research informants being students of Yari Junior High School Padang, which were taken by random sampling. The results of this study indicate that the students of Yari Junior High School Padang understand the verses about people with special needs quite well. This can be seen from the answers to the following problems. First, the students at Yari Junior High School Padang understand people with special needs generally. Second, the students at Yari Junior High School Padang understand the meaning of the verses of the Qur'an about people with special needs, especially those contained in Surah An-Nur: 61 and Surat 'Abasa: 2. Third, the attitudes of students at Yari Junior High School Padang to the people with special needs are in accordance with what Allah has commanded in the Qur'an.